Genetic Characteristic and Global Transmission of Influenza A H9N2 Virus - Hu, Mingda; Jin, Yuan; Zhou, Jing; Huang, Zhisong; Li, Beiping; Zhou, Wei; Ren, Hongguang; Yue, Junjie; Liang, Long (Frontiers in Microbiology, 2017)
The H9N2 virus has been demonstrated to donate its genes to other subtypes of influenza A virus, forming new reassortant virus which may infect human beings. Understanding the genetic characteristic and the global transmission patterns of the virus would guide the prevention and control of potentially emerging avian influenza A virus. In this paper, we hierarchically classified the evolution of the H9N2 virus into three main lineages based on the phylogenetic characteristics of the virus. Due to the distribution of sampling locations, we named the three lineages as Worldwide lineage, Asia-Africa lineage, and China lineage. Codon usage analysis and selective positive site analysis of the lineages further showed the lineage-specific evolution of the virus. We reconstructed the transmission routes of the virus in the three lineages through phylogeography analysis, by which several epicenters for migration of the virus were identified. The hierarchical classification of the lineages implied a possible original seeding process of the virus, starting from the Worldwide lineages to the Asian-Africa lineages and to the China lineages. In the process of H9N2 virus global transmission, the United States was the origin of the virus. China Mainland, Hong Kong SAR, Japan and Korea were important transfer centers. Based on both the transmission route and the distribution of the hosts in each lineage, we concluded that the wild birds’ migration has contributed much to the long-distance global spread of the virus, while poultry trade and people’s lifestyle may have contributed to the relatively short-distance transmission in some areas of the Asia and Africa.